Media management and artificial intelligence : understanding media business models in the digital age - Connock, Alex (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This cutting-edge textbook examines contemporary media business models in the context of Artificial Intelligence and digital transformation. AI has dramatically impacted media production and distribution, from recommendation engines to synthetic humans, from video-to-text tools to natural language models. "AI is really the change agent of the media industry," answered a natural language generation model when AI was 'asked' about the subject of this book. "It will open incredible opportunities." This book seeks to explore them. The media is examined through four sections. 'Principles' maps business models and the key tools of AI. 'Platforms' covers distribution channels in Games, Streamers, Social Networks, Broadcast and Digital Publishing. 'Producers' covers the engines of content-making, including Scripted, Entertainment, Factual, Content Marketing, Creators and Music. Finally, 'Pioneers' covers emerging sectors of Podcasters, Esports, the Metaverse and other AI-driven developments. Then in each chapter, a standard value creation model is applied, mapping a single sector through development, production, distribution and monetisation. Diverse case studies are analysed from India, Nigeria, South Korea, South Africa, France, the Netherlands, US, UK, Denmark and China - around creative entrepreneurship, revenue models, profit drivers, rights and emerging AI tools. Questions are provided for each case, whilst key learning points and chapter summaries cement learning. Applied and technology-focused, this text offers core reading for advanced undergraduate and postgraduates studying Media Management - or the relationship between Entertainment, Media and Technology. Online resources include chapter-by-chapter PowerPoint slides and an Instructor's Manual with further exercises and case studies"--
Media management & artificial intelligence -- Media business models -- Overview of AI -- Games -- Social networks -- Streamers -- Broadcasters -- Digital publishers -- Scripted -- Entertainment -- Factual -- Marketing content -- Creators -- Music -- Podcasters -- Esports -- The metaverse -- Future of the media business.
OCLC-licensed vendor bibliographic record.
Keywords: Mass media -- Management -- Data processing; Artificial intelligence -- Industrial applications; BUSINESS & ECONOMICS / Industries / Media & Communications Industries; BUSINESS & ECONOMICS / Strategic Planning